Age, Educational Level and Gender in Self-concept of People with Retinitis Pigmentosa - López Justicia, María Dolores; Fernández Castillo, Antonio; Fernández, Carolina; Polo, Mª Tamara (Anales de Psicología / Annals of Psychology, 2011)
Since the construct of self-concept plays a key role in personali-ty and because this concept can be weakened by the appearance of a se-rious disease such as RP, the research question of the present study was to examine the relationship between age, educational level and gender in the self-concept of 35 adults with this diagnosis. The instrument used was the Tennessee Self-Concept Scale and one questionnaire for demographic, socioeconomic and educational information. The results showed that age was associated with moral self-concept, which was higher in older persons. Family self-concept, however, was lower in older persons. Less educated persons had a lower mean physical self-concept. In relation to gender the results showed that women had a higher physical self-concept than men. We conclude that intervention during the initial years after diagnosis should be designed to palliate the effects of retinitis pigmentosa on psy-chological well-being and to provide counseling for individuals and their families to reduce disruptions in family life.